Programação para o ensino de estudo de textos didáticos utilizando aplicativos - Lima, Tuane de Oliveira (2020)
Although fundamental to students' school life, they are rarely systematically taught how to study. The demands of today's world make it necessary to teach them how to create strategies to study autonomously, having the possibility to learn something directly from the available materials, which can be a didactic text. Considering that studying didactic texts is an essential repertoire for the student's autonomy, and based on Behavior Analysis, the objectives were to develop and evaluate the application of a computerized programming to teach how to study didactic texts. The program focused on different target behaviors: inspecting the text, locating and highlighting important information, paraphrasing, building schematics and conceptual maps, and elaborating questions on the topic. The activities were created using technological applications such as Google Forms, Socrative and Wordwall. Ten students from the 3rd to the 6th year of elementary school participated in this study, half from public schools and half from private schools. Participation took place online and remotely, via Zoom platform. The study was organized in six stages: Prerequisite Evaluation, Evaluation of the Initial Directory, Application of the Teaching Program, Partial Evaluation (after each programming step), Evaluation of the Final Directory and Generalization Evaluation. The results showed an improvement in the performance of the participants in seven of the ten behaviors selected for evaluation: inspecting the text before reading, discussing the general subject of the text before reading, locating and inferring information from the text, paraphrasing the text read, graphically highlighting the ideas the text, construct schematics and conceptual maps and elaborate questions about what has been studied. These results indicate that skills that make up studying can be taught from the beginning of schooling and that such teaching can occur through computerized programming